1981
DOI: 10.1128/jb.148.1.333-340.1981
|View full text |Cite
|
Sign up to set email alerts
|

Loss of virulence during culture of Aeromonas salmonicida at high temperature

Abstract: The effect of growth temperature on the loss of virulence of the fish pathogen Aeromonas salmonicida was investigated. Three virulent strains were grown in Trypticase soy broth at temperatures ranging from 22 to 30 degrees C. Growth at a higher-than-optimal temperature (26 to 27 degrees C for the three strains studied) resulted in the selection of spontaneous attenuated derivatives in the initial bacterial population. For example, virulent bacteria represented less than 10% of the population of a culture grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
104
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(112 citation statements)
references
References 16 publications
6
104
2
Order By: Relevance
“…The challenge stain was characterized and compared to an avirulent strain (1102). Autoagglutination, haemagglutination, serum resistance and adhesion (propereties displayed by strain 184/86) have been attributed to the presence of the A-layer by several workers (Evenberg, Van Boxtel, Lugtenberg, Schurer, Blommaert & Bootsma 1982;Evenberg & Lugtenberg 1982;Ishiguro, Kay, Ainsworth, Chamberlain, Austen, Buckley & Trust 1981;Kay, Buckley, Ishiguro, Phipps, Monete & Trust 1981;Munn, Ishiguro, Kay & Trust 1982;Trust, Canotice & Atkinson 1980;Udey & Fryer 1978). The A layer has been shown to be hydrophobic in nature (Phipps, Trust, Ishiguro & Kay 1983) and Parker & Munn (1984) demonstrated that Aeromonas salmonicida possessing the A-protein were more hydrophobic than strains devoid of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge stain was characterized and compared to an avirulent strain (1102). Autoagglutination, haemagglutination, serum resistance and adhesion (propereties displayed by strain 184/86) have been attributed to the presence of the A-layer by several workers (Evenberg, Van Boxtel, Lugtenberg, Schurer, Blommaert & Bootsma 1982;Evenberg & Lugtenberg 1982;Ishiguro, Kay, Ainsworth, Chamberlain, Austen, Buckley & Trust 1981;Kay, Buckley, Ishiguro, Phipps, Monete & Trust 1981;Munn, Ishiguro, Kay & Trust 1982;Trust, Canotice & Atkinson 1980;Udey & Fryer 1978). The A layer has been shown to be hydrophobic in nature (Phipps, Trust, Ishiguro & Kay 1983) and Parker & Munn (1984) demonstrated that Aeromonas salmonicida possessing the A-protein were more hydrophobic than strains devoid of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Fuller, Pilcher & Fryer (1977) described an extracellular leucocytolytic factor isolated from virulent strains of A. salmonicida, and an extracellular protein which was immunogenic and afforded protection was described by Cipriano (1982). However, the rough-smooth transformation of A. salmonicida readily occurs on certain artificial media (Ishiguro, Kay, Ainsworth, Chamberlain, Austen, Buckley & Trust 1981;Evenberg, Van Boxtel, Lugtenberg, Schurer, Blommaert & Bootsma 1982). The rough variant, which autoagglutinates in saline, is highly virulent and possesses an additional outer layer on the cells (Udey & Fryer 1978).…”
Section: Introductionmentioning
confidence: 99%
“…This gene encodes the subunit protein (A-protein) of the paracrystalline surface array (A-layer) produced by this organism. The A-layer enhances the virulence of A. salmonicida (Ishiguro et al 1981) and protects A. salmonicida from the bactericidal activity of both immune and nonimmune sera (Munn et al 1982). Because vapA gene is a virulence factor of A. salmonicida, PCR analysis with oligonucleotide primers directed at vapA can be used to provide information on the potential virulence of this strain.…”
Section: Discussionmentioning
confidence: 99%